2015
DOI: 10.4238/2015.september.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Interactome analysis and design of inhibitors against selected protein targets of Ser/Thr protein kinase (STPK) signaling pathways in Mycobacterium tuberculosis H37Rv

Abstract: ABSTRACT. Tuberculosis continues to be a major cause of mortality worldwide despite significant advances in chemotherapy and development of the BCG vaccine. Although curable, the tuberculosis treatment period (6-9 months) presents many concerns, including patient noncompliance and the development of drug toxicity and drug resistance. This study aimed to understand the protein-protein interactions of key proteins involved in the Mycobacterium tuberculosis STPK signal transduction pathway (such as PknB, PknE, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Functional attributes of PknE substrates were already depicted with a working model in earlier report [36]. It is noteworthy that the substrates PstP and Wag31 identified as substrates for PknE by us using in vivo proteomic approach was predicted as probable substrate in a in silico based study [35].…”
Section: Proteomics Studies Suggest Pkne Could Regulate Sigb Responsimentioning
confidence: 72%
See 1 more Smart Citation
“…Functional attributes of PknE substrates were already depicted with a working model in earlier report [36]. It is noteworthy that the substrates PstP and Wag31 identified as substrates for PknE by us using in vivo proteomic approach was predicted as probable substrate in a in silico based study [35].…”
Section: Proteomics Studies Suggest Pkne Could Regulate Sigb Responsimentioning
confidence: 72%
“…Substrates with higher scores are depicted in Figure 1. Besides, the approaches used by us, homologous protein mapping model that encompasses data from experimentally validated substrates and STRING database suggested substrates for pknE [34,35]. However, these in silico predictions await experimental validation.…”
Section: Proteomics Studies Suggest Pkne Could Regulate Sigb Responsimentioning
confidence: 99%
“…The alkaloid cryptolepine, isolated from the dried roots of Cryptolepis sanguinolenta, has attracted much attention as its multiple biological activities, such as antimicrobic, antidiabetic, and anti-inflammatory activity . Our previous work first reported that cryptolepine and its derivative L-03 exhibited good fungicidal activity against B.…”
Section: Introductionmentioning
confidence: 99%